Improving 4C Skills Through the Application of Gamification-Based Interactive Evaluation Media Using Flipped Classroom Integrated Project Based Learning Model - Firdiawan Ekaputra; Wilda Syahri; Fuldiaratman Fuldiaratman (EduLine: Journal of Education and Learning Innovation, 2024)
This study sought to ascertain how well students' 4C skills were improved by utilizing gamification-based interactive evaluation materials in conjunction with a flipped classroom and project-based learning approach. Pre-experimental research with a quantitative approach and one sample class was the methodology employed in this study. Students enrolled in the Jambi University Chemistry Education Study Program's course on chemistry learning curriculum creation served as the study's samples. A questionnaire was used to collect data on the 4C competencies of the pupils. The normalcy of the variation in the students' 4C skills outcomes was examined. The data from the sample class is normally distributed and parametric tests can be performed if the significance value is higher than 0.05. In this study, one sample t-test was employed for hypothesis testing. To find out how well gamification-based interactive evaluation materials combined with a flipped classroom and project-based learning approach improve 4C abilities, hypothesis testing was done. The study's conclusion is that students' 4C skills can be effectively improved by implementing gamification-based interactive evaluation materials in conjunction with a flipped classroom and project-based learning approach.